2002
DOI: 10.1016/s0272-6963(02)00004-9
|View full text |Cite
|
Sign up to set email alerts
|

Print versus electronic surveys: a comparison of two data collection methodologies

Abstract: This paper compares the responses of consumers who submitted answers to a survey instrument focusing on Internet purchasing patterns both electronically and using traditional paper response methods. We present the results of a controlled experiment within a larger data collection effort. The same survey instrument was completed by 416 Internet customers of a major office supplies company, with approximately 60% receiving the survey in paper form and 40% receiving the electronic version. In order to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(145 citation statements)
references
References 25 publications
(42 reference statements)
6
137
0
2
Order By: Relevance
“…An individual approach to each of the chosen respondents ensured a high response rate. Boyer, Olson, Calantone, and Jackson (2002) confirm that electronic surveys have fewer missing responses in comparison with printed surveys.…”
Section: Methodology Study Design and Implementationsupporting
confidence: 59%
“…An individual approach to each of the chosen respondents ensured a high response rate. Boyer, Olson, Calantone, and Jackson (2002) confirm that electronic surveys have fewer missing responses in comparison with printed surveys.…”
Section: Methodology Study Design and Implementationsupporting
confidence: 59%
“…Online research surveys do not appear to create response bias (Boyer et al 2002;de Leeuw and Nicholls 1996;Tanriverdi 2001). Data collection began four days prior to the beginning of a seven-day national holiday in China when many members planned trips.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that the differences between online and paper-and-pencil forms for the same questionnaire are negligible (Boyer, Olson, Calantone, & Jackson, 2002;Denscombe, 2006;Ferrando & Lornzo-Seva, 2005;Leung & Kember, 2005;Lucia, Herrmann, & Killias, 2007). We used Blau and Caspi's (2008) questionnaire with minor changes made to adapt the questions to the current population.…”
Section: Research Tools and Proceduresmentioning
confidence: 99%